Exploring the challenges confronting the west Africa climate system - M.E, Emetere; M.L, Akinyemi; M.E, Ojewumi; B.M, Muhammad; ., . (International Journal of Engineering and Technology, 2018)
The peculiar location of West Africa on the World map suggests that the region is prone to be under severe atmospheric influences from other regions. With a population of over 300 million people, the human activity and its corresponding impact on the climate system of the region is worth noting. The meteorological exploration of funded projects like AERONET, AMMA, DACCIWA etc. in West Africa shows the peculiarity of the danger that life-forms in West Africa might be facing in the next two decades. The documentation of salient discoveries over the West Africa Monsoon and whose challenges may be the possible answers to questions on the West Africa climate system. A re-view on the satellite exploration within 2002-2006 shows the anomalies which require intense concern by all and sundry.Â Â